1998
DOI: 10.1021/ma970832q
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Polymer Architecture in Strengthening Polymer−Polymer Interfaces:  A Comparison of Graft, Block, and Random Copolymers Containing Hydrogen-Bonding Moieties

Abstract: A series of styrene-d 8/4-hydroxystyrene graft and block copolymers has been prepared by “living” radical and anionic techniques for use in interfacial strengthening studies at the polystyrene/poly(2-vinylpyridine), PS/PVP, interface. The following copolymers in which A and B segments represent poly(styrene-d 8) and poly(4-hydroxystyrene), respectively, have been prepared:  poly(A-graft-B), poly(B-graft-A), poly(B-block-A-block-B), poly(A-block-B-block-A-block-B-block-A). The poly(4-hydroxystyrene) segments we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
59
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 35 publications
(73 reference statements)
1
59
0
Order By: Relevance
“…In a separate study, PS/P(2VP) interfaces were also reinforced by multiblock copolymers composed of S and poly (4-hydroxystyrene). This system also demonstrated that the pentablock copolymer was a more effective interfacial modifier than the triblock copolymer, [11] in agreement with our recent results [4 -6,34] that suggest that blocky copolymers are the most effective interfacial strengtheners.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a separate study, PS/P(2VP) interfaces were also reinforced by multiblock copolymers composed of S and poly (4-hydroxystyrene). This system also demonstrated that the pentablock copolymer was a more effective interfacial modifier than the triblock copolymer, [11] in agreement with our recent results [4 -6,34] that suggest that blocky copolymers are the most effective interfacial strengtheners.…”
Section: Introductionsupporting
confidence: 92%
“…The effectiveness of random copolymers to reinforce polymers interfaces has also been widely investigated [11,12,15,21,22,[33][34][35][36][37][38] and was found to be dependent on the monomer composition [22]. In the case of PðS f -ran-MMA 12f Þ; where f is the monomer composition, the compositionally asymmetric P(S 0.7 -ran-MMA) displayed the greatest reinforcement of the PS/PMMA interface out of a range of P(S-ran-MMA) compositions studied [21].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 A significant amount of effort has been devoted to developing efficient methods for accurately controlling polymer topology and architecture with the aim of preparing polymeric materials with new properties. 4 Many concepts and synthetic approaches have been developed to prepare macromolecules with various architectures and topologies, including dendrimers [5][6][7][8] and hyperbranched polymers, 9 -15 supramolecular polymers, 16 -21 cylindrical and spherical polymers, [22][23][24] polymers having folded structures, [25][26][27] molecular wires, 28 -30 metal-core polymers, 31,32 and polymeric nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, it is worth noting that graft copolymers are largely used for the compatibilization of immiscible polymer blends. [15][16][17][18][19][20][21] In the past decade, investigations on polymer blends have intensified significantly because they offer a convenient alternative to developing totally new polymers. Polymer blends can be tailored to meet the requirements of specific applications.…”
Section: Introductionmentioning
confidence: 99%